2018
DOI: 10.4172/2329-6887.1000261
|View full text |Cite
|
Sign up to set email alerts
|

Immune-potentiation of Pneumococcal Capsular Polysaccharide Antigen using Albumin Microparticles

Abstract: Microparticles (MPs) offer several advantages as unique vaccine delivery system, including the ease to manufacture, targeted delivery of antigen payload, sustained antigen release and possible role as an immuneadjuvant. In this study, we evaluated albumin matrix for pneumococcal (Pnc) serotype specific capsular polysaccharide (PS) antigen MPs. Microencapsulation of Pnc PS was successful with a product yield of >72%. The MP size, 1-5 μm, and negative zeta potential (-26.5 mV) were optimized to ensure effective-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…To evaluate the efficacy of the pneumococcal polysaccharide-protein conjugate vaccines, the total IgG antibody production, IgG functionality (OPA assay using homologous strain), immunological memory, and protection in challenge studies were measured. , In our study and similar to previous reports, immune response evaluation showed that 19F-PhaC beads promoted the production of specific and high IgG titers than the group immunized with alum . Interestingly, the nonconjugated mix of 19F CPS and PHB beads did not induce detectable IgG titer, which suggested that codelivery of antigens and PHB beads is required for induction of an immune response. , In addition, IgG titer were superior when mice were vaccinated with 19F-PhaC than with 19F-TT, which was used as a positive control (Figure B).…”
Section: Discussionsupporting
confidence: 82%
“…To evaluate the efficacy of the pneumococcal polysaccharide-protein conjugate vaccines, the total IgG antibody production, IgG functionality (OPA assay using homologous strain), immunological memory, and protection in challenge studies were measured. , In our study and similar to previous reports, immune response evaluation showed that 19F-PhaC beads promoted the production of specific and high IgG titers than the group immunized with alum . Interestingly, the nonconjugated mix of 19F CPS and PHB beads did not induce detectable IgG titer, which suggested that codelivery of antigens and PHB beads is required for induction of an immune response. , In addition, IgG titer were superior when mice were vaccinated with 19F-PhaC than with 19F-TT, which was used as a positive control (Figure B).…”
Section: Discussionsupporting
confidence: 82%
“…Inability of vaccine candidates to invoke suitable immune responses leads to failed vaccine development [ 40 ]. There is a necessity for the development of potent as well as safe adjuvants to deliver new generations of vaccines against infectious (e.g., pneumonia) and non-infectious (e.g., cancer) diseases [ 41 , 42 ]. The invention of Baker et al provides composition and methods to stimulate immune responses using nanoemulsion and an inactivated pathogen via mucosal delivery [ 43 ].…”
Section: Applications Of Colloidal Carriersmentioning
confidence: 99%